Scale Pretesting - Matt C. Howard (Practical Assessment, Research, and Evaluation, 2018)
Scale pretests analyze the suitability of individual scale items for further analysis, whether through judging their face validity, wording concerns, and/or other aspects. The current article reviews scale pretests, separated by qualitative and quantitative methods, in order to identify the differences, similarities, and even existence of the various pretests. This review highlights the best practices and objectives of each pretest, resulting in a guide for the ideal applications of each method. This is followed by a discussion of eight questions that can direct future research and practice regarding scale pretests. These questions highlight aspects of scale pretests that are still largely unknown, thereby posing a barrier to their successful application. Accessed 1,632 times on https://pareonline.net from April 05, 2018 to December 31, 2019. For downloads from January 1, 2020 forward, please click on the PlumX Metrics link to the right.
Keywords: Test Construction